2021
DOI: 10.2478/acve-2021-0031
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Disseminated Pseudomonas Aeruginosa Infection in a Captive Green Iguana (Iguana iguana)

Abstract: Infections with various bacteria, especially gram-negative aerobes, are a well-recognized problem in captive cold-blooded animals with immunocompromised health status, or in those kept under poor conditions. Pseudomonas is one of the most represented genera. Here, we present a case of fatal disseminated infection caused by Pseudomonas aeruginosa in a captive green iguana kept at the “Pionirska dolina” Zoo in Sarajevo, Bosnia and Herzegovina. At necropsy, severe stomatitis, pneumonia, hepatitis and nephritis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition, in our study, Haemogregarina stepanowi-infected turtles revealed alterations in hematocrit and hemoglobin concentrations. However, similar parameters and values could be common findings in captive reptiles with malnutrition and other chronic conditions [30,31].…”
Section: Discussionmentioning
confidence: 61%
“…In addition, in our study, Haemogregarina stepanowi-infected turtles revealed alterations in hematocrit and hemoglobin concentrations. However, similar parameters and values could be common findings in captive reptiles with malnutrition and other chronic conditions [30,31].…”
Section: Discussionmentioning
confidence: 61%